2020
DOI: 10.1002/elsc.202000048
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ethyl acetate from glucose by Kluyveromyces marxianus, Cyberlindnera jadinii and Wickerhamomyces anomalus depending on the induction mode

Abstract: Ethyl acetate is currently produced from fossil carbon resources. This ester could also be microbially synthesized from sugar‐rich wastes of the food industry. Wild‐type strains with GRAS status are preferred for such applications. Production of ethyl acetate by wild‐type yeasts has been repeatedly reported, but comparative studies with several strains at various induction modes are largely missing. Here, synthesis of ethyl acetate by three yeasts with GRAS status, Kluyveromyces marxianus DSM 5422, Cyberlindne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In addition, a significant amount of acetyl-CoA formed from glucose does not enter the TCA cycle but condenses with ethanol to form ethyl acetate. A similar effect has been also shown for yeast Kluyveromyces marxianus, which produce ethyl acetate in significant quantities under iron-limited conditions [53].…”
Section: Discussionsupporting
confidence: 69%
“…In addition, a significant amount of acetyl-CoA formed from glucose does not enter the TCA cycle but condenses with ethanol to form ethyl acetate. A similar effect has been also shown for yeast Kluyveromyces marxianus, which produce ethyl acetate in significant quantities under iron-limited conditions [53].…”
Section: Discussionsupporting
confidence: 69%
“…Esters composed the second largest group of aroma compounds produced by K. marxianus . Esters are formed by a condensation reaction between alcohols (ethanol or higher alcohols) and acetyl-CoA (for acetate esters) or acyl-CoA (for ethyl esters) [ 55 , 56 ]. It is well known that ester production is positively affected by precursor availability, i.e., the alcohols released by K. marxianus in this study, and the presence of lactose in skyr required for acetyl-CoA formation [ 43 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ethyl acetate (solvent aroma), ethyl butyrate (pineapple), ethyl hexanoate (aniseed, apple), ethyl octanoate (sour apple) and isoamylacetate (banana, pineapple) were produced in large quantities, close to or higher than the thresholds. The ability of K. marxianus strains to produce esters, in particular ethyl acetate, has been frequently reported [ 38 , 56 , 59 , 60 ]. Previously, Leclercq-Perlat et al identified similar aroma compounds produced by K. marxianus in a cheese medium (e.g., hexanal, 2 (3)-methylbutanal, butanol, 2 (3)-methylbutanol, 2-methylpropanol) and reported a link between the levels of isoamylacetate and ethyl acetate, and ester-like fruity odours [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In media with an iron shortage, microbial growth is limited by available energy resources in the cell [47]. Under iron deficiency, the conversion of organic substance falls; most acetyl-CoA does not enter the TCA cycle and is condensed with the formation of ethyl acetate [48]. As shown in the work [49], the increase in iron concentration in cultivation media activates the TCA cycle, respiratory chain and oxidative phosphorylation in Y. lipolytica.…”
Section: Ironmentioning
confidence: 99%